From balance to performance: The mediating role of job motivation and engagement among married employees in FDI enterprises - Quoc Viet Nguyen; Phan To Uyen; Hai Ninh Nguyen (Global Business & Finance Review (GBFR), 2024)
Purpose: This study delves into the dynamics of work-life balance and its effects on job motivation, engagement, and performance among married employees within Foreign Direct Investment (FDI) enterprises in Vietnam, aiming to uncover the mediating roles of job motivation and engagement. Design/methodology/approach: Employing Structural Equation Modeling (SEM) and Partial Least Squares Structural Equation Modeling (PLS-SEM), this research meticulously analyzes the causal relationships between work-life bal- ance, job motivation, job engagement, and job performance. Findings: The study establishes that an improved work-life balance significantly boosts job motivation and engage- ment among married employees, which subsequently leads to enhanced job performance. These results underscore the critical need for FDI enterprises to implement and uphold supportive work-life balance policies. Research limitations/implications: While offering valuable insights, this research is primarily focused on married employees in FDI enterprises in Vietnam, which may limit the generalizability of the findings to other contexts or demographics. Future studies could broaden the scope to include diverse employee groups and organizational settings. Originality/value: This investigation enriches the literature by offering a deeper understanding of the dynamics between work-life balance and employee performance, especially in the context of FDI enterprises in Vietnam, and presents practical guidance for enhancing organizational practices.
Keywords: 650; Job motivation; Job engagement; Work-life balance and job performance; Married employees; FDI enterprises